Fatigue crack behaviour: comparing three-point bend test and wedge splitting test data on vibrated concrete using Paris' law - S. Seitl; T. Thienpont; W. De Corte (Fracture and Structural Integrity)
The fatigue behaviour of concrete has become more important for the design of constructions due to the desire to build slimmer structures, which are more sensitive to fatigue loading. This article aims to evaluate and compare the fatigue crack propagation rate in vibrated concrete for four different stress ratios using the Paris-Erdogan law. The data evaluation in this article is based on crack mouth opening displacement (CMOD) measurements from cyclic three-point bending tests on single edge notched beams and from wedge splitting tests on notched cubes, obtained from experiments at Ghent University. For this study, finite element analysis is used to obtain a mathematical relationship between the CMOD and the relative crack length a/W, as well as a relationship between the stress intensity ratio ∆K and a/W. The obtained mathematical relationships were then combined with the measured CMOD values to correlate the test data to the Paris-Erdogan law. Herein, the crack propagation rate da/dN is plotted against the corresponding stress intensity range ∆K in a log-log graph. In a final step, the Paris-Erdogan law parameters C and m were obtained through linear curve fitting on the data points from the obtained graphs. The parameters C and m are then used to compare and evaluate the fatigue crack behavior in vibrated concrete, and the differences between the results from the three-point bend tests and wedge splitting tests.